2023
DOI: 10.1111/pcn.13521
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rest‐activity rhythm and longitudinal brain changes underlying late‐life cognitive decline

Abstract: Aim:The neurobiological substrates underlying the relationship of circadian rest-activity rhythm (RAR) alteration with accelerated late-life cognitive decline are not clearly understood. In the present study, the longitudinal relationship of objectively measured circadian RAR with in vivo Alzheimer disease (AD) pathologies and cerebrovascular injury was investigated in older adults without dementia. Methods: The present study included 129 participants without dementia who participated in the KBASE (Korean Brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Furthermore, the Rotterdam Study indicated earlier L5 onset with increased dementia risk in the next 2 years, which supports our findings. In contrast, several other studies have indicated that delayed acrophase is associated with cognitive decline or dementia 31,32 . Our study has the advantages of a large sample size and inclusion of a healthy elderly population excluding early‐onset dementia cases, providing sufficient statistical power for our analyses.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the Rotterdam Study indicated earlier L5 onset with increased dementia risk in the next 2 years, which supports our findings. In contrast, several other studies have indicated that delayed acrophase is associated with cognitive decline or dementia 31,32 . Our study has the advantages of a large sample size and inclusion of a healthy elderly population excluding early‐onset dementia cases, providing sufficient statistical power for our analyses.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, several other studies have indicated that delayed acrophase is associated with cognitive decline or dementia. 31,32 Our study has the advantages of a large sample size and inclusion of a healthy elderly population excluding early-onset dementia cases, providing sufficient statistical power for our analyses. However, further systematic reviews and meta-analyses are needed to thoroughly investigate the association between circadian phase and incident dementia.…”
Section: Clinical Neurosciencesmentioning
confidence: 99%